Penyelesai Sengketa Lingkungan Laba Pura Dalem Agung (Persepektif Hukum Adat) - I Wayan Titra Gunawijaya; Ni Wayan Silawati (Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja, 2021)
The trigger for conflict between humans is an interest in mutual ownership which is not their right, so that it can cause a sense of dissatisfaction. This occurs due to a lack of information and understanding between rights and responsibilities. Land disputes occur because of these matters which can be resolved by the laba pura as a social institution that has desa adat law as its basis. Through the right approach and good data collection, research has resulted that customary law has a very strong power to protect every element of life under it, of course also refers to the applicable laws and regulations as a guide, a reviewer of related problems. In addition to civil legal channels, land disputes can be resolved through deliberation, of course, through fierce mediation by both parties, involving various witnesses and mutually reinforcing evidence regarding the position of the disputed land. Deliberation is carried out by summoning both parties and witnesses who can corroborate alibis as arguments for the recognition of the land. Through the final decision, the land which was actually owned by the Desa Adat as a laba pura was handed back by the brahman family as laba pura.